Perceptions of parenting behavior by adolescents: the development of the Malaysian Parenting Behavior Inventory - Zulkefly, Nor Sheereen; Barra, Sharisse May Mate; Yahya, Amira Najiha; Baharudin, Rozumah (Universiti Putra Malaysia Press, 2021)
We conducted a study with the aims of examining adolescents’ perceptions of their mother’s and father’s parenting behavior and developing a new Malaysian Parenting Behavior Inventory (MPBI). In Phase One, we recruited 903 adolescents using the proportionate to size sampling technique. The results of the exploratory factor analyses of the MPBI Mother and Father scales revealed four underlying factor structures: Warmth, Monitoring, and Harsh Discipline were somewhat similar to those in past findings and theory, and Indigenous centered on religious and cultural values in parenting. In Phase Two, using an independent sample of adolescents, we replicated the factor structure of Study One with confirmatory factor analysis, resulting in strong model fit estimates. We conclude that the MPBI has good initial psychometric properties and is culturally influenced. The MPBI may be useful for prevention and intervention programs in clinical and non-clinical settings, including providing valuable information on factors pertinent to parent-adolescent interactions.